Factors associated with level of food safety knowledge among form four students In Hulu Langat district, Selangor - S., Syahira (Community Health Society Malaysia, 2019)
Background: Food safety protects consumers from risks of foodborne diseases and addresses the proper handling, preparing and storing of food. With foodborne diseases still remaining an important cause of morbidity and mortality worldwide, food safety continues to be emphasized and enhancing consumer food safety knowledge and practice is one important measure to prevent foodborne diseases. Although there are efforts of food safety education in schools, there is still limited research regarding food safety knowledge and practice amongst consumers especially school students. Therefore, this research aims to determine the level and factors associated with food safety practice among form four students in Hulu Langat district, Selangor.